According to the AUGUSTUS Trial Apixaban (Eliquis ® ) was Found to Be Safer than Vitamin K Antagonists in Patients with Non-Valvular Atrial Fibrillation with Acute Coronary Syndrome and/or Percutaneous Coronary Intervention - Company Pfizer (Столичная издательская компания, 2019)
Pfizer Company Press Release.